1960
DOI: 10.1113/jphysiol.1960.sp006582
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic rate and heat loss of fat and thin men in heat balance in cold and warm water

Abstract: suggested that deep cooling might be of little importance in practice. However, it has been reported (Keatinge, 1960 a) that although the rate at which men's rectal temperatures fell in water at 150 C was closely related to their subcutaneous-fat thickness, their early metabolic response to the cold immersion was not, and the metabolic rates of thin men only rose substantially above those of the fat men during the later part of immersions, when the thin men's rectal temperatures fell. The present studies of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

1961
1961
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(47 citation statements)
references
References 33 publications
(44 reference statements)
7
39
0
Order By: Relevance
“…Clearly, the exercising, limbs considerably increase the overall heat conductance (27). Considering these factors and research findings, several investigators have concluded that rest is more effective than armleg exercise in maintaining a higher core temperature when individuals are immersed in cold water (3,10,12,15).…”
Section: Security Classification Of This Page(whaa Data Entmed)mentioning
confidence: 99%
“…Clearly, the exercising, limbs considerably increase the overall heat conductance (27). Considering these factors and research findings, several investigators have concluded that rest is more effective than armleg exercise in maintaining a higher core temperature when individuals are immersed in cold water (3,10,12,15).…”
Section: Security Classification Of This Page(whaa Data Entmed)mentioning
confidence: 99%
“…By virtue of its lower water content, fat tissue has a lower thermal conductivity than lean tissue (Cohen, 1977;Cooper and Trezek, 1971) and, hence, when fat tissue is distributed in a continuous subcutaneous layer (such as the layer of blubber in pinnipeds and cetaceans) it may provide substantial thermal insulative benefits. Studies of humans immersed in cool water (15-20°C) show that individuals who have greater adiposity cool down more slowly than leaner individuals and do not need to elevate their metabolic rate as much to defend this slower cooling rate (Cannon and Keatinge, 1960;Buskirk et al, 1963;Kollias et al, 1974;Keatinge, 1978;Hayward and Keatinge, 1981;Tikuisis et al, 1988;GlickmannWeiss et al, 1991). These studies indicate that obesity in humans also provides an insulative advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding this lower T sk , more rapid convectional heat losses occur, with T c falling two-five times more quickly compared with that observed in air at the same temperature (Hong, 1984). When immersion is accompanied by exercise, the rate of T c decline is often (Cannon and Keatinge, 1960;Keatinge, 1961), though not always accelerated (Craig and Dvorak, 1968;McArdle et al, 1984). This disparity stems not only from differences in water temperature and subject adiposity, but from variations in both exercise intensity and mode.…”
Section: Introductionmentioning
confidence: 99%